An Intelligent m-Healthcare System for Improving the Service Quality in Domestic Care Industry. Issue 2 (2020) - Lam, H.Y.; Tang, Y.M.; Tang, Valerie; Wu, C.H.
Abstract: Due to declining fertility rate and increasing life expectancy, population aging has become a growing problem in Hong Kong. Domestic elderly service providers and public health institutions have been suffering from a shortage of experienced staff for elderly healthcare, which has led to a drop in both the quality and efficiency of the local elderly service. With the rising popularity of mobile applications and the betterment of machine vision technology, this paper describes the design of an Intelligent m-Healthcare System (ImHS) for relieving the manpower pressure on local elderly service providers by lowering the technical threshold and simplifying staff training process. Face recognition technology is applied to identify the elderly by searching and tracing the elderly medical record through the FaceAPI service. In addition, the proposed ImHS provides the immediate insight into healthcare knowledge for users, which lowers the occurrence of Adverse Drug Event (ADE) and shortens the duration of pill distribution process. By conducting a case study in a local elderly home, the proposed system allowed the nursing staff to better allocate healthcare resources and to improve the operation effectiveness and efficiency.